FUNGSI BAHASA MENURUT LEECH PADA PUISI KECOA PEMBANGUNAN KARYA W.S. RENDRA: IMPLEMENTASI PENGAJARAN SASTRA DI MTS [The function of language according to Leech in the poem 'Kecoa Pembangunan' by W.S. Rendra: The Implementation of Literature Teaching at MTs] - Arika Rini (TOTOBUANG, 2021)
The issue  in this article discusses about the understanding meaningcontext of poetry that has been not  be studied from structural linguistics  since the early 20th century. The purpose of this research is  studying and analyzing contemporary poetry WS Rendra using the function of Leech language and  enriching class VIII KD 3.7 material. and 4.7 on the building blocks of poetry text and deducing the meaning of the poetry text. Throughthe qualitative descriptive analysis method, WS Rendra's poetry was described by analyzing the lines in the verse of his poetry. The function of Leech language can be studied and analyzed in poetry literature, especially contemporary poetry.  Five of the  language functions, there is only one function that cannot be examined from the poem. It is the phatic function because the poem in entitled 'Kecoa Pembagunan' contains social criticism which used the words of satire and ridicule in every  lines of the sentences. The function of the Leech language can be implemented in teaching because the results of the analysis can be integrated with the building blocks of poetry. As my suggestion,  the teachers should expand the study of language functions from several experts to improve and expand literary material, especially poetry.Permasalahan yang dibahas dalam artikel ini tentang adanya pemahaman makna  pada konteks puisi  yang belum bisa dikaji dari linguistik struktural yang sudah ada sejak awal abad 20. Tujuan penelitian untuk mengkaji dan menganalisis puisi kontemporer WS Rendra dengan mengunakan fungsi bahasa Leech serta memperkaya materi kelas VIII KD 3.7 dan 4.7 pada unsur pembangun teks puisi serta menyimpulkan makna teks puisi. Dengan metode analisis deskriptif kualitatif, puisi WS Rendra dideskripsikan maknanya dengan menganalisis baris-baris dalam bait puisinya. Fungsi bahasa Leech dapat dikaji dan dianalisis pada sastra puisi, terutama puisi kontempoer. Dari lima fungsi bahasa hanya satu fungsi yang tidak bisa dikaji dari puisi tersebut, yaitu fungsi fatis. Hal ini dikarenakan puisi yang berjudul ‘Kecoa Pembagunan’ berisi kritik sosial yang menggunakan kata kias sindiran dan ejekan pada baris-baris kalimatnya. Fungsi bahasa Leech dapat diimplementasikan dalam pengajaran karena dari hasil analisis dapat terintegrasi dengan materi unsur-unsur pembangun puisi.  Saran penulis, guru sebaiknyalebih memperluas kajian fungsi bahasa dari beberapa ahli untuk meningkatkan dan memperluas materi sastra terutama puisi.